Trends in stochastic analysis : festschrift in honour of Heinrich von Weizsäcker - Blath, Jochen; Mörters, Peter; Scheutzow, Michael; Von Weizsäcker, Heinrich (London Mathematical Society lecture note series, 2009)
Presenting important trends in the field of stochastic analysis, this collection of thirteen articles provides an overview of recent developments and new results. The articles cover a wide range of topics, from an alternative set-up of rigorous probability to the sampling of conditioned diffusions.